Observations on the Application of the LOMLOE Assessment in the Hight School after its Implementation - Sánchez Liendo, Eduardo (Avances en Supervisión Educativa, 2025)
The evaluation system, as introduced by Organic Law 3/2020, of 29 December, which amends Organic Law 2/2006, of 3 May, on Education, is based on a challenging curricular architecture aimed at providing evaluation with a competency-based nature. For this approach to be successful, we need to change both the methodology and the evaluation procedures themselves, so that all of them reflect the aforementioned competency-based nature. Once completed the implementation of the curriculum of the so-called LOMLOE, it is appropriate to point out some technical incidents which we have detected while applying the evaluation system of this law (specifically, we refer to the grading procedures of the competences developed by Castile and León) and which can endanger not only the competency-based system itself, but also the decisions that, in the case of High School Level, a teaching team must make based on the result of the evaluation of the competences themselves.